Relationship Between Mother's Knowledge About Breastfeeding and Mother's Behavior in Providing Exclusive Breastfeeding in The Work Area of Technical Implementation Unit of the Public Health Center Barong Tongkok - Yuanita, Ester; Carol Sipasulta, Grace; Nur Imamah, Indah (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Mother's milk is a good nutrient to protect babies against infection and prevent malnutrition because it contains important nutrients needed by the baby's body. Breast milk is the best natural nutrition for babies because it contains the energy and substances needed for the first six months of a baby's life. Breastfeeding is very important, but babies are still not getting exclusive breastfeeding.  Objective: To determine the relationship between mother's knowledge about breastfeeding and mother's behavior in providing exclusive breastfeeding in the Work Area of ??Technical Implementation Unit of the Public Health Center Barong Tongkok.  Methods: The design of this study used a descriptive correlation with a cross-sectional approach, carried out in May 2022. The statistical test used is Chi Square if the t count (p value) < 0.05, then the hypothesis Ha is accepted and Ho is rejected.  Results and Discussion: The statistical test of mother's knowledge about breastfeeding with mother's behavior in exclusive breastfeeding obtained a value of 0.003 <0.05.  Conclusion: There is a relationship between mother's knowledge about breastfeeding and mother's behavior in providing exclusive breastfeeding in the Work Area of ??Technical Implementation Unit of the Public Health Center Barong Tongkok